Bioactivity of Methanolic and Aqueous Extracts of Laurus nobilis L. from Different Origins - Dias, Maria Inês (2013)
Laurus nobilis L. (Laureaceae), commonly known as laurel, is a native plant from the Mediterranean region. Most widely used as culinary spice, it is also consumed as infusion to treat some gastrointestinal problems (Dall’Acqua et al., 2009) and has been reported as a rich source of bioactive compounds namely, essential oils and phenolic compounds (Dadalioğlu et al., 2004; Dias et al., 2013). In the present work, methanolic and aqueous extracts of wild and cultivated L. nobilis were studied for their in vitro antitumor (against five different human tumor cell lines) and antimicrobial (antibacterial and antifungal) activities. Furthermore, a two-dimensional principal component analysis (PCA) was used to understand how each extract act differentially towards specific bacterial and fungal species, and also selected human tumor cell lines. Both assayed factors, origin (wild or cultivated) and extract type (methanolic or aqueous) act in a differentiated manner; i.e., the same evaluated parameter gave sometimes statistically significant differences regarding laurel origin, but no effect at all from extract type, or vice versa. Nevertheless, the extract type induced the most marked changes in bioactivity of laurel samples. From the PCA biplot, it became clear that wild samples were more effective to inhibit tumor cell lines growth, especially HeLa, MCF7, NCI-H460 and HCT15. It was also observed that methanolic extracts tended to have higher antimicrobial activity, except for Aspergillus niger, Aspergillus. fumigatus and Penicillium verrucosum. The differences in bioactivity might be related to the higher phenolic compounds content (flavonols, flavones and even, total phenolic compounds) presented by methanolic extracts,. The most interesting finding in this work was the bioactive specificity of each laurel extract, considering its wild or cultivated origin. Moreover, from the PCA biplot obtained is possible to choose the combination extract type/origin with potentially highest effect against determined bacteria, fungi or tumor cell line, depending on the objective of the study.